Bisnis Perjalanan Haji dan Umrah oleh Nonmuslim Menurut Tinjauan Hukum Islam - Laode Nursyah Dendi; Azwar Azwar; Khaerul Aqbar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This study aims to determine the review of Islamic law on the management of hajj and umrah businesses by non-Muslims. This research is a descriptive library research, with a socio-historical approach and reconstructs istidlāl and legal istinbāt used by fiqh scholars. The results of the study show that: (1) the principles and laws of the origin of muamalah and interacting with non-Muslims are permissible as long as in terms of, boundaries and corridors of muamalah and are not included in the case of ritual worship, aqidah, and belief; (2) using Hajj and Umrah travel business services managed by non-Muslims is permissible because it is included in the muamalah al-ijārah/leasing area; (3) as a form of prudence, in using Hajj and Umrah business services managed by non-Muslims, it is necessary to pay attention to the following: non-Muslim services are used when there is no (found) Hajj and Umrah organization performed by Muslims, must be safe and not there is something that is detrimental to the Muslims, and there is no element of deviation from the creed of the Muslims; (4) with various considerations of the benefits and impacts that will be caused, it is recommended to Muslims to put the Muslims first in any case, including in using the services of business trips for Hajj and Umrah.